20 Gut microbiota in human adults with irritable bowel syndrome differs from healthy controls. (5th December 2017) - Liu, YH; Wang, Y; Wen, S; Zhang, T; Tang, L
Abstract : Background: Recent evidence suggests that there is a link between irritable bowel syndrome (IBS) and microbiota in the gut. The onset and maintenance of IBS may be caused by gut microbiota, but the causes of the pathophysiology of this disorder are unknown. Method: 25 patients who fulfilled Rome III criteria for IBS and 29 age- and gender-matched healthy controls were chosen in this study. The total bacterial DNA isolated from the two populations was investigated through amplicon pyrosequencing of the V3–V4 regions of the 16S ribosomal RNA gene. Results: The composition of bacteria in the groups differed between healthy controls and IBS subgroups from phylum to the genus level. Synergistetes phylum (p=0.016), Bacilli class (p=0.006), Lactobacillales order (p=0.006), Enterobacteriales order (p=0.02), the families Streptococcaceae (p=0.009), Enterobacteriaceae (p=0.02), and Enterococcaceae (p=0.001), and the genera Streptococcus (p=0.002), Enterobacter (p=0), Klebsiella (p=0.006), and Enterococcus (p=0.001) exhibited higher levels in IBS patients compared with healthy controls. By contrast, Clostridia class (p=0.024), Betaproteobacteria class (p=0.019), Clostridiales order (p=0.024), the families Bacteroidaceae (p=0.049), Desulfovibrionaceae (p<<0.01), and Lachnospiraceae (p=0.012), and the genera Bacteroides (p=0.049) and Roseburia (p=0.012) had lower levels in IBS patients. The genera Turicibacter and Collinsella were most abundant in 51–60 year old patients, followed by 31–40 year old IBS patients. We also detected Acinetobacter and Campylobacter belonging to Proteobacteria phylum in female IBS patients, but not in male patients. Conclusion: There were differences in faecal microbiota between IBS patients and healthy controls. The faecal microbiota of patients with IBS is associated with significant increases in detrimental and decreases in beneficial bacterial groups. Acknowledgment: Supported by grants from National Program on Key Basic Research Project (973 Program, 2013CB531405), and the National Natural Science Foundation of China (NSFC, No. 81641029 and 81370113).